Seismic performance and new design procedure for chevron-braced frames. - Marino, Edoardo M. (Earthquake engineering & structural dynamics.)
The paper is concerned with the seismic design of steel-braced frames in which the braces are configured in a chevron pattern. According to EuroCode 8 (EC8), the behaviour factor q, which allows for the trade-off between the strength and ductility, is set at 2.5 for chevron-braced frames, while 6.5 is assigned for most ductile steel moment-resisting frames. Strength deterioration in post-buckling regime varies with the brace's slenderness, but EC8 adopts a unique q value irrespective of the brace slenderness. The study focuses on reevaluation of the q value adequate for the seismic design of chevron-braced frames. The present EC8 method for the calculation of brace strength supplies significantly different elastic stiffnesses and actual strengths for different values of brace slenderness. A new method to estimate the strength of a chevron brace pair is proposed, in which the yield strength (for the brace in tension) and the post-buckling strength (for the brace in compression) are considered. The new method ensures an identical elastic stiffness and a similar strength regardless of the brace slenderness. The advantage of the proposed method over the conventional EC8 method is demonstrated for the capacity of the proposed method to control the maximum inter-storey drift. The q values adequate for the chevron-braced frames are examined in reference to the maximum inter-storey drifts sustained by most ductile moment-resisting frames. When the proposed method is employed for strength calculation, the q value of 3.5 is found to be reasonable. It is notable that the proposed method does not require larger cross-sections for the braces compared to the cross-sections required for the present EC8 method.